A parametric study of green water impact on a container ship. (15th March 2020) - Kudupudi, Ravindra Babu; Bhattacharyya, A; Datta, R
ABSTRACT: The influence of wavelength, wave steepness and bow rake angle ( α ) on the green water occurrence and peak pressure on a container ship deck is numerically investigated. Numerical simulations are performed using a commercial CFD solver, where a VOF method is employed to capture the free surface. The approach is validated using previously published experimental results. The time histories of the evolution of green water pressure on the deck, as well as the peak pressure magnitude, are studied at forward speed conditions. The results indicate that peak pressure due to green water increases significantly with vessel speed for all the wavelengths investigated. Investigations with a range of bow rake angle ( α ) indicate that the impact pressure decreases with the increase of ' α '. For the range of ' α ' chosen (0 degrees to 30 degrees), the differences in impact pressure are within 20% of the value for the vertical bow.